x(5x-2)(x+9)=

Simple and best practice solution for x(5x-2)(x+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(5x-2)(x+9)= equation:


Simplifying
x(5x + -2)(x + 9) = 0

Reorder the terms:
x(-2 + 5x)(x + 9) = 0

Reorder the terms:
x(-2 + 5x)(9 + x) = 0

Multiply (-2 + 5x) * (9 + x)
x(-2(9 + x) + 5x * (9 + x)) = 0
x((9 * -2 + x * -2) + 5x * (9 + x)) = 0
x((-18 + -2x) + 5x * (9 + x)) = 0
x(-18 + -2x + (9 * 5x + x * 5x)) = 0
x(-18 + -2x + (45x + 5x2)) = 0

Combine like terms: -2x + 45x = 43x
x(-18 + 43x + 5x2) = 0
(-18 * x + 43x * x + 5x2 * x) = 0
(-18x + 43x2 + 5x3) = 0

Solving
-18x + 43x2 + 5x3 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(-18 + 43x + 5x2) = 0

Factor a trinomial.
x((-9 + -1x)(2 + -5x)) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9

Subproblem 3

Set the factor '(2 + -5x)' equal to zero and attempt to solve: Simplifying 2 + -5x = 0 Solving 2 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -5x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = 0 + -2 -5x = 0 + -2 Combine like terms: 0 + -2 = -2 -5x = -2 Divide each side by '-5'. x = 0.4 Simplifying x = 0.4

Solution

x = {0, -9, 0.4}

See similar equations:

| x(x-3)=x+5x+7 | | 4x=x^3-3x^2 | | 2x=x+5(-x) | | (8x+2)(8x+2)= | | x^4-2x^2+6=3x^2 | | 4x(x+3)=3x+9 | | s-9=9 | | (8x+9)(8x+9)= | | 8(t-6)+7t=5(3t+3)-8 | | 6x+2=-28x | | 0.10x+0.5(12-x)=.10(1) | | 4x(x+2)=3x+9 | | (b+6)(b-4)= | | 175=(25)(7)+b | | 3(2m+5)-12= | | 4x^3+23x^2+34x-10=0 | | 2x-5-3x-4= | | 0.90x+.05(2-x)=.10(-67) | | (5t^2-t-7)(2t^2+5t-1)= | | 14-3/5= | | 4(-2r+3)-2(1-6r)= | | 3x+7=49 | | (8t^2-t-5)(4t^2+8t-1)= | | x^2-13y^2=101 | | 130=14a-10 | | 1.3-5=5.4 | | 16a+10=90 | | -3x-4=-22 | | 5x-10=50-x | | 5(x-2)-8x=-24 | | 0.5s=10 | | (4x-5)(x^2-3x+3)= |

Equations solver categories